Rubinstein-Taybi Syndrome; A Case Report - SORKHI, Hadi; ASGHARI VOSTACOLAEE, Yasser; GHABELI JUIBARI, Ali (Iranian Journal of Child Neurology, 2011)
Objective Rubinstein-Taybi Syndrome is a rare genetic disorder with characteristic featuresincluding downward slanting palpebral fissures, broad thumbs and halluces,and mental retardation. Systemic features may involve cardiac, auditory,ophthalmic, endocrine, nervous, renal and respiratory systems. This syndromeis sporadic in nature and has been linked to microdeletion at 16p 13.3 encodingCREB-binding protein gene (CREBBP). We report a 15-years-old girl, a knowncase of chronic renal failure, with downward slanting palpebral fissures towardthe ears, hypertelorism, short stature, beaked nose, micrognathia, strabismus,dental anomalies, large toes, broad thumbs, and mental retardation. Key words: Rubinstein-Taybi syndrome; chromosome 16p 13.3; mentalretardation; CBP gene.